determine x e y tais que:
[2x+y] = [11]
[2x-y] = [9]
Soluções para a tarefa
Respondido por
18
Pelo método da substituição:
2x + y = 11
2x - y = 9
1ª) 2x + y = 11
y = 11 - 2x
2ª) 2x - y = 9
2x - (11- 2x) = 9
2x - 11 + 2x = 9
2x + 2x = 9 + 11
4x = 20
x = 20/4
x = 5
Volta a 1ª onde parou para calcular valor de y.
y = 11 - 2x
y = 11 - 2.(5)
y = 11 - 10
y = 1
S[ x= 5 ; y = 1]
2x + y = 11
2x - y = 9
1ª) 2x + y = 11
y = 11 - 2x
2ª) 2x - y = 9
2x - (11- 2x) = 9
2x - 11 + 2x = 9
2x + 2x = 9 + 11
4x = 20
x = 20/4
x = 5
Volta a 1ª onde parou para calcular valor de y.
y = 11 - 2x
y = 11 - 2.(5)
y = 11 - 10
y = 1
S[ x= 5 ; y = 1]
rayssaevelly611:
Muito Obrigada :)
Perguntas interessantes
Sociologia,
1 ano atrás
Matemática,
1 ano atrás
Português,
1 ano atrás
Biologia,
1 ano atrás
Química,
1 ano atrás